Press, Populism and Resistance. Crónica sentimental de España by Manuel Vázquez Montalbán in the Magazine Triunfo - Polizzi, Assunta (Populismo y propaganda: entre el presente y el pasado, 2020)
In the fall of 1969, Manuel Vázquez Montalbán published five reports entitled Crónica sentimental de España, where he analyzes everyday life to reflect the sentimental evolution of Spaniards from the 1940s to the 1960s and highlights the mechanisms by which popular culture forges the collective imagination, while the Francoism makes it a transmitter of moral conduct norms within a program of populist propaganda. The aim of this study is to go through the narrative construction of the journalistic text and its focus on the populist discourse which becomes a proposal of resistance.